2019
DOI: 10.1002/nop2.266
|View full text |Cite
|
Sign up to set email alerts
|

African American women's perceptions of the meaning of support groups for improving adherence to hypertension treatment: a conceptual model

Abstract: Aim To investigate the meaning of support groups and the features of these groups that African American (AA) women view as improving adherence to high blood pressure (HBP) treatment. The study generated a conceptual model to illuminate features of these groups that influence adherence of AA women to HBP treatment. Design Qualitative research. Methods Used focus groups and open‐ended questions to obtain the views of 26 eligible AA women, recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The significant role of the support groups in controlling patients with T2DM and/or hypertension, especially in LMICs with a rising burden of diabetes, is well documented. For example, studies have reported that support groups can enhance diabetes knowledge and psychosocial functioning [ 24 , 25 ], improve diabetes outcomes [ 26 , 27 ], and enhance self-management behaviors [ 27 , 28 ]. Therefore, it is of fundamental importance to take advantage of support groups when providing services for patients with diabetes or other chronic health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The significant role of the support groups in controlling patients with T2DM and/or hypertension, especially in LMICs with a rising burden of diabetes, is well documented. For example, studies have reported that support groups can enhance diabetes knowledge and psychosocial functioning [ 24 , 25 ], improve diabetes outcomes [ 26 , 27 ], and enhance self-management behaviors [ 27 , 28 ]. Therefore, it is of fundamental importance to take advantage of support groups when providing services for patients with diabetes or other chronic health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Social isolation, low income, depression, or psychological distress have been ascertained as causes of withdrawal during treatment [3,16,18,19]. Statistical analyses from the investigation of African American women, Latino migrants, seasonal farmworkers, Chinese people, and people from south-west Nigeria have illustrated that social supports could promote patient adherence to treatment via sharing information and assisting in bringing about life style changes [20,21,22,23]. Surprisingly, about 10.3% of hypertension patients develop hypertensive resistance during the treatment regimen, which may be typified by a lower response to medications [24].…”
Section: Introductionmentioning
confidence: 99%